Creating marketing magic and innovative future marketing trends : proceedings of the 2016 Academy of Marketing Science (AMS) Annual Conference /: proceedings of the 2016 Academy of Marketing Science (AMS) Annual Conference. ([2017]) - Unknown
No abstract available